ANALYSIS OF EXCHANGE RATES AND INTEREST RATES ON INDONESIA'S NON-OIL AND GAS EXPORT VALUE - Denny Saputera; Rizal Budi Santoso; Dwi Fauziansyah Moenardy; Rizqi Muttaqin; Rina Ariyanthi Dewi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study evaluates the impact of exchange rates and interest rates on Indonesia's non-oil and gas exports from 2006 to 2022, recognizing the sector's importance in the Indonesian economy. Data reveal a significant increase in non-oil and gas exports from USD 155.9 billion in 2019 to USD 275.9 billion in 2022, driven by strong global demand from major economies such as China, the United States, and India. The analysis indicates that exchange rates have a positive effect on non-oil and gas exports, though the impact is statistically insignificant with a p-value exceeding 0.05. In contrast, interest rates exhibit a significant negative impact on export values, with a p-value of 0.022, suggesting that higher interest rates may reduce export volumes. Assumption testing reveals no issues with multicollinearity, autocorrelation, or heteroscedasticity, ensuring the validity of the results. In conclusion, while exchange rates positively affect exports, the impact is not significant; interest rates, however, have a significant negative effect, indicating the need for lower interest rate policies to support the growth of Indonesia's non-oil and gas exports.